Perbandingan Strategi Personal Branding Amry Sophia MUA dengan Lia Makeup Melalui Portofolio di Media Sosial - Eny Widhia Agustin; Indah Indi Afifah; Maharani Irfina Putri; Diah Rosmaya; Maria Deo Haro; Amri Dian Pratiwi; Lia Puji Astuti (Garina, 2026)
This study aims to analyze the comparison of personal branding strategies implemented by Amry Sophia MUA and Lia Makeup through social media portfolios. The research used a qualitative approach with a comparative case study design. Data were collected through semi-structured interviews, digital observations on Instagram and TikTok accounts, and documentation of both participants’ portfolio content. Data analysis was conducted through verbatim transcription, thematic analysis, and triangulation between interview results and digital observation findings. The results show that Amry Sophia MUA builds personal branding through a consistent visual identity characterized by a modern glam look and Thailand makeup style that appears soft, flawless, and elegant. The target market is more focused on wedding makeup and young adult brides-to-be. Meanwhile, Lia Makeup presents a flawless natural look that is more flexible and suitable for a wider audience. Lia Makeup is also supported by a media team, making the content management more structured and consistent. Both MUAs use Instagram as a visual portfolio platform and TikTok as a medium to show makeup processes, tutorials, and audience interaction. In addition, quick responses, customer testimonials, and authenticity are important factors in building trust and a professional image on social media. Therefore, this study indicates that strong personal branding can be developed through visual consistency, appropriate content strategies, audience segmentation, and effective communication with potential clients.